A cerebral cortex-like structured metallized elastomer for high-performance triboelectric nanogenerator - Park, Moon Kyu; Lee, Seokmin; Ko, Yongmin; Cho, Jinhan (Elsevier BV, 2023)
The advancement of wearable electronics, particularly triboelectric nanogenerators (TENGs), relies on the development of flexible, stretchable, and compressible electrodes that possess a large active surface area, high electrical conductivity, and excellent mechanical stability and deformability. However, existing elastomeric electrodes face challenges in meeting all of these requirements. Herein, we present a novel approach to address these limitations and create electrodes with elastomeric properties, stable metal-like electrical conductivity, and an expanded active surface area. For this goal, we perform an assembly of metal nanoparticles (NPs) in toluene and amine-functionalized organic linkers in alcohol onto the thiol-functionalized, embossed-structured elas-tomer. Particularly, the assembly process involves ligand exchange reaction-mediated metal NPs and subjecting them to solvent-swelling/deswelling of the embossed PDMS. This process induces the formation of cerebral cortex-like structured elastomer electrode, which is subsequently electroplated with Ni. The resulting electrodes exhibit metal-like electrical conductivity, elastomer-like flexibility, and cerebral cortex-like structure with sub-stantially large surface area and high stress relieving properties. When combined with an intaglio-structured dielectric PDMS electrode, the device exhibits impressive TENG performance, surpassing the performance of conventional TENGs. This approach provides a basis for developing and designing a variety of high-performance flexible electronics, including TENGs.